Transitional cell carcinoma in orthotopic ileal neobladder 12 years after radical cystectomy - Hadži-Djokić, Jovan; Pejčić, Tomislav; Andrejević, Vladan; Djurašić, Ljubomir (Vojnosanitetski pregled, 2017)
Introduction. Some cases of secondary adenocarcinoma developing in the replaced bowel segment of urinary diversions have been reported so far. Secondary adenocarcinoma develops 20 years  after surgery in about 0.5% of those in whom an ileal segment is used. There have been several reports in the literature describing extensions of transitional cell carcinoma (TCC) from the distal urether into an ileal conduit. Histology of loop tumor in 50% was TCC. The site of tumors in the majority of cases is the area at the uretheral orifices or the stoma. Case report. We presented a rare case of transitional cell carcinoma in an orthotopic ileal neobladder 12 years after radical cystoprostatectomy and ileal neobladder with the substitution by the procedure Camey II. A 65-year-old man with high-grade urothelial carcinoma of neobladder underwent partial resection of neobladder and right nephroureterectomy. Pathological analysis revealed high-grade urothelial carcinoma to the ileal neobladder (G II, Stage T2b). The patient died of laryngeal cancer a year after the surgery. Conclusion. Surgery of tumors in orthotopic neobladders is possible if diagnosed in time. In the presented case surgery resulted only in a decrease in the capacity of the neobladder without having an effect on the continence itself.
Keywords: urinary bladder; neoplasms; cystectomy; ileum; colonic pouches; recurrence